Integration of catalyst and nucleophile in oxometal aminobis(phenolate) complexes with ammonium iodide pendant arm groups - Peuronen Anssi; Salojärvi Esko; Salonen Pasi; Lehtonen Ari (Elsevier, 2022)
An amine bisphenol ligand with an ammonium iodide group in the pendant arm (H2L) reacts with V, Mo and U oxometal precursors to form oxovanadium(V), dioxomolybdenum(VI) and dioxouranium(VI) species, respectively. In methanol solutions, vanadium(V) and molybdenum(VI) form 1:1 complexes [VO(OMe)(L)]I·2MeOH and [MoO2(L)(H2O)]I·2MeOH, where the cationic charge in the pendant arm is counterbalanced by an iodide anion. Uranium(VI) forms a complex in which the anionic charge of uranate complex unit is compensated by the cationic pendant arm. The complex crystallises as a co-crystal containing a neutral ligand precursor, namely [UO2(L)(OAc)]·[H2L]I·4MeOH. The oxovanadium(V) complex combines a Lewis acid, i.e. a pentacoordinated metal centre with a Lewis basic iodide moiety, which makes it a suitable catalyst for the coupling of CO2 with styrene oxide. The role of the ammonium moiety of the ligand is to carry the iodide nucleophile in the reaction.